20. KNOWLEDGE AND PRACTICE ON USING PERSIONAL PROTECTIVE EQUIPMENT OF HEALTH STAFFS AT THE NATIONAL EYES HOSPITAL, IN 2021 (Vietnam Journal of Community Medicine, 2023)
Background: Using protective equipment in medical activities is a very urgent requirement.Protective means in addition to the function of protecting health workers during professional practicealso have a particularly important position to ensure patient safety.Objectives: Describe the knowledge and practice on using personal protective equipment of medicalstaff at the National Eye Hospital and analyze some related factors.Methods: Cross-sectional survey, quantitative research.Results: The rate of health workers with knowledge on using personal protective equipmentreached 71,2%. The rate of health workers with practices on using personal protective equipmentreached over 80%. There are 4 factors related to knowledge on using personal protective equipmentincluding: age, working position, working time and professional qualifications. Three factors relatedto practices on using personal protective equipment including: Gender, working position and time oftraining on infection control (p
Keywords: Infection control, related factors, health workers.